Analysis and Quality Measurement of SITEDI Sub-System Against User Satisfaction Using WebQual 4.0 and End-User Computing Satisfaction (EUCS) Methods - Prasetya, Ananda; Efrilianda, Devi Ajeng (Department of Computer Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang, 2023)
One of the efforts in handling educational challenges in the era of technological development is the development of the Thesis Information System for Dissertation Thesis (SITEDI). SITEDI is an information system that facilitates the thesis administration process starting from the presentation of the subject matter to the final exam managed by Universitas Negeri Semarang (UNNES). Therefore, it is necessary to measure the quality of SITEDI performance based on user satisfaction to facilitate the evaluation process of SITEDI as a quality student service in the future. The research method used in this study is a combination of WebQual 4.0 and End-User Computing Satisfaction (EUCS). The variables used include usability quality, information quality, service interaction quality, format, and timeliness. The sample used was 135 respondents with purposive sampling technique. The results of the analysis that have been carried out conclude that simultaneously the variables of usability quality, information quality, service interaction quality, format, and timeliness have an influence on user satisfaction by 62.5%. WebQual 4.0 variables, namely service interaction quality, information quality, and usability quality sequentially have a significant influence on user satisfaction with an effect size of 0.092, 0.069, and 0.028. Meanwhile, the EUCS variables, namely format and timeliness, do not have a significant influence on user satisfaction.